The AI Revolution in Mental Health: Can Technology Bridge the Treatment Gap? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2024)
The AI Revolution in Mental Health: Can Technology Bridge the Treatment Gap? The global mental health crisis presents a formidable challenge, characteri...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care